2014
DOI: 10.1097/mao.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Prognostic Factors for Long-term Postoperative Hearing Results After Canal Tympanoplasty for Congenital Aural Stenosis

Abstract: The absence of EAC cholesteatoma and anterolateral position of the malleus/incus complex with respect to the stapes are considered useful in predicting long-term favorable hearing results after canal tympanoplasty for CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…Our similar results between syndromic and nonsyndromic cases correlate with a prior study from Sakamoto and colleagues. 17 In a prior series, no significant differences in audiologic outcomes were found between cases in which an OCR was performed compared with cases in which an intact and mobile ossicular chain was encountered. 10 In the current larger series, statistically significant differences between these 2 groups were found in 4 of the 6 audiometric parameters assessed.…”
Section: Discussionmentioning
confidence: 87%
“…Our similar results between syndromic and nonsyndromic cases correlate with a prior study from Sakamoto and colleagues. 17 In a prior series, no significant differences in audiologic outcomes were found between cases in which an OCR was performed compared with cases in which an intact and mobile ossicular chain was encountered. 10 In the current larger series, statistically significant differences between these 2 groups were found in 4 of the 6 audiometric parameters assessed.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies analysing the clinical features of CAS involved small sample sizes, and no studies focused on the stability of the hearing outcomes567. This study uses the largest sample of CAS, providing guidance in consultation and emphasizing important aspects for long-term follow-up.…”
mentioning
confidence: 99%
“…Patients with stenosis sizes of 2 mm or less are at high risk for developing cholesteatoma and should undergo surgery; however, the data in the present study challenged this viewpoint. To date, there are no large sample studies focusing on the clinical features and long-term outcomes of CAS, and no studies have described the important parameter of measuring the diameter of EAC 5 6 7 8 9 10 11 .…”
mentioning
confidence: 99%
“…Thus, there was no significant difference in the same surgical technique between the cholesteatoma and no cholesteatoma groups, including Δ ABG, preoperative and postoperative ABG 20 . A previous study suggested that the Jahrsdoerfer score (modified) was less useful in terms of predicting long-term hearing prognosis after canal tympanoplasty for CAS in 25 patients 6 . Nevertheless, the mean Jahrsdoerfer score in the no cholesteatoma group was higher than that in the cholesteatoma group, and the Jahrsdoerfer score is a factor that affects postoperative ABG.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stenosis sizes of 2 mm or less are at high risk for developing cholesteatoma and should undergo surgery; however, the data in the present study challenged this viewpoint. To date, there are no large sample studies focusing on the clinical features and long-term outcomes of CAS, and no studies have described the important parameter of measuring the diameter of EAC [5][6][7][8][9][10][11] . The aim of the present study was to comprehensively evaluate the clinical features and long-term outcomes of CAS, and challenge the previous viewpoint.…”
mentioning
confidence: 99%